THEORETICAL AND METHODOLOGICAL ASPECTS OF FORMING A SYSTEM FOR EVALUATING STRATEGIC MANAGEMENT OF INNOVATIVE AND ENVIRONMENTALLY FRIENDLY ENTREPRENEURSHIP - CHOBITOK, Viktoriіa; SHABANOV, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the research is determined by the need to improve strategic approaches to managing innovation and environmental processes in entrepreneurial activity, taking into account national characteristics, global environmental trends, and the need to harmonize economic and environmental interests. The scientific novelty lies in the development of a comprehensive concept of strategic management of innovative and environmental entrepreneurship, which integrates the principles of sustainable development, innovative management, and environmental forecasting.The practical significance of the research lies in the possibility of using the results obtained to form effective strategies for enterprises aimed at environmental modernization, increasing competitiveness, and responsibility to society and the environment.In the context of environmental instability and growing pressure from international environmental standards, strategic management of innovative and environmentally friendly entrepreneurship is becoming particularly relevant for Ukraine. Enterprises that implement environmental innovations are forced to operate in conditions of unstable legal regulation, limited financial resources, and insufficiently developed environmental awareness in the business environment. Under such conditions, it is extremely important to form a strategic vision for the development of innovative and environmentally friendly entrepreneurship that would ensure not only economic efficiency but also environmental protection.The purpose of the study is to substantiate and develop theoretical and methodological aspects of forming a system for evaluating strategic management of innovative and environmentally friendly entrepreneurship.At the present stage, strategic management of the innovative and environmentally friendly development of enterprises is becoming particularly important, as it combines economic efficiency with environmental responsibility.An analysis of statistical data for 2022–2024 showed a trend towards a reduction in the number of enterprises emitting pollutants in most regions of Ukraine. This indicates a gradual greening of production, modernization of technologies, and improvement in the effectiveness of environmental management. At the same time, there has been a significant increase in patent activity, especially on the part of national applicants, indicating a strengthening of the innovative potential of the economy.In 2024, the number of applications for inventions and utility models increased by more than a third compared to the previous period, which is a sign of increased applied development in the field of environmental technologies. It has been found that the key factors for the strategic development of enterprises are the integration of environmental standards into management systems, the introduction of digital monitoring tools, and the development of partnership clusters. Thus, innovative and environmental entrepreneurship is emerging as an important component of Ukraine's sustainable economic growth.The study substantiates that strategic management of innovative and environmental entrepreneurship is a key tool for forming competitive advantages of enterprises in the context of sustainable development, digital transformation, and environmental challenges.The results of the study can serve as a basis for the formation of effective development strategies for Ukrainian enterprises in the post-war period with a focus on environmental modernization, growth in patent activity, and the development of cross-sectoral partnerships and cluster formations.
Keywords: innovative and environmental entrepreneurship; strategic management; sustainable development; assessment methods; frameworks; environmental policy; patent activity